Investigating SnOx/Graphene Oxide heterostructure for methane sensing and its application as a tunable light absorber for optoelectronic devices - Manoj Kumar; Purnendu Shekhar Pandey; M. Sudhakara Reddy; Anita Gehlot; Santosh Kumar Choudhary; Gyanendra Kumar Singh; Balkeshwar Singh (PLoS ONE, 2025)
This study investigates the optical and electronic properties of SnOx/Graphene Oxide (SnOx/GO) heterostructures, focusing on their sensitivity and selectivity to methane adsorption and its tunable light absorption capabilities across different wavelength ranges. By categorizing SnOx/GO heterostructures into four types based on the oxygen mole fraction (x) of SnOx, notable differences are observed in their light absorption, extinction coefficient, and reflectance. Among these, Type-C heterostructures demonstrate the highest absorption coefficient (~1.8 × 10⁵ cm ⁻ ¹), indicating strong potential for UV and visible light applications. Building upon the optimized Type-C SnOx/GO heterostructure, we further examine the effect of varying concentrations of methane molecules adsorbed on its surface. This leads to the classification of four additional heterostructure types- Type-I to Type-IV which are based on the methane molecules concentration adsorbed on the surface of an optimized SnOx/GO heterostructure. The interaction with methane further modulates the optoelectronic properties of heterostructure, with Type-II heterostructures demonstrating the highest extinction coefficient (~8.0 at 1000 nm) and strong near-infrared absorption. In contrast, Type-IV structures, characterized by the highest methane concentration, show a significant increase in reflectance (~0.85) and a reduction in absorption. Additionally, an energy distribution analysis of various atmospheric gases, such as CH₄, H₂O, and CO₂ were conducted to evaluate the selectivity of SnOx/GO heterostructure based sensors. The aim was to ensure minimal interference from other ambient gases. The analysis revealed that CH₄ exhibits a more negative energy state, indicating higher stability and a greater affinity for adsorption on the sensor surface compared to the other atmospheric gases. This stabilization highlights the interaction dynamics of the material, reinforcing its potential for diverse applications, including UV absorption, infrared transparency, and trace methane detection. Overall, these findings establish SnOx/GO heterostructures, particularly the Type-C variant with an optimal oxygen mole fraction (x), as promising candidates for advanced optical and methane gas-sensing technologies.